Proceedings of the 2018 8th International Conference on Social Science and Education Research (SSER 2018) 2018
DOI: 10.2991/sser-18.2018.65
|View full text |Cite
|
Sign up to set email alerts
|

The Influencing Factors and Improvements of College Students' Abilities in Innovation and Entrepreneurship - From the Perspective of School and Society

Abstract: The cultivation of college students' innovative and entrepreneurial abilities is closely related to school and society. From the school's point of view, the influencing factors of innovation and entrepreneurship capabilities, such as the innovation and entrepreneurship curriculum system to be improved, the innovation and entrepreneurship practice training system needs to be strengthened, etc. are analyzed, and the improvements of creating innovation and entrepreneurship education system, and strengthenning inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The entrepreneurial intention of college students has received a lot of attention. Studies have shown that gender, personality traits, entrepreneurial knowledge, and desire for achievement can be used to predict EI levels, along with family education, entrepreneurial orientation from the government, and regional entrepreneurial atmosphere as external factors [7].…”
Section: Introductionmentioning
confidence: 99%
“…The entrepreneurial intention of college students has received a lot of attention. Studies have shown that gender, personality traits, entrepreneurial knowledge, and desire for achievement can be used to predict EI levels, along with family education, entrepreneurial orientation from the government, and regional entrepreneurial atmosphere as external factors [7].…”
Section: Introductionmentioning
confidence: 99%